FROM THE HISTORY OF THE JUDICIAL SYSTEM IN TURKISTAN (Scientific journal of the Fergana State University, 2023)
The article provides information about the judicial system of Turkistan, its structure, types of courts. There is information about the activities of public officilas (judges) in the judicial system, requirements for the position of a judge. It also covers the study of the regional judicial system of the Russian Empire, its policy towards it, changes in the courts and the attitude of the local population towards them.